FREQUENCY AND RISK FACTORS OF METABOLIC SYNDROME IN WOMEN WITH TYPE 2 DIABETES - Maheshwary, Neeta; Naveed, Shabnam; Ghafoor, Rabia; Ali, Zeeshan; Ahmed, Syed Masroor (Pakistan Journal of Physiology, 2016)
Background: ‘Metabolic disorder’ is defined as a group of metabolic risk factors, and its diagnosis requires at least three out of central obesity, elevated BP, elevated fasting plasma glucose (FBS), high serum triglycerides (TG), and low high-density lipoprotein (HDL) levels. The objective of this study was to assess the frequency and risk factors of metabolic syndrome (MetS) in type 2 diabetic female patients. Methods: This was a cross-sectional study carried out from January, 2015 to July, 2015. A total of 155 diabetic women aged 18–70 years were included using convenience sampling method. Detailed medical history, physical examination and laboratory assessment of fasting blood glucose, HbA1c, and lipid profile was completed for every patient. Results: The frequency of MetS was 96.1% in the studied diabetic women. Low HDL was the commonest component (98.5%) followed by hypertension (98.2%) and central obesity (95.9%). Central obesity, hypertension, raised TG, low HDL and high LDL were associated with the MetS. Conclusion: Frequency of MetS and all components of MetS were found very high in diabetic women. Prevention strategies for cardiovascular disease may be implemented through health education and prompt treatment to reduce the burden of complications. Pak J Physiol 2016;12(2):26–8